Training and Development as Determinants of Job Performance: A Nigerian Conceptual Perspective - Dangana, Nuhu; Oyidi, Cletus M.; Jev, Amos (Lembaga Yasin AlSys, 2025)
This conceptual paper explores the complex interplay between training, development, and job performance, with a focused lens on the Nigerian workplace. It posits that human capital is the foundational asset for driving organizational productivity and that structured, evidence-based training and development initiatives are essential for enhancing employee efficiency, innovation, and service delivery. Despite the recognized importance of workforce development, many Nigerian public and private institutions continue to face persistent performance deficits, often attributable to inadequate, outdated, or misaligned training efforts. Drawing on human capital theory and expectancy theory, the paper examines how learning, motivation, and competence intersect to shape individual and organizational outcomes. Within the Nigerian context, the paper identifies systemic challenges including insufficient funding, fragile institutional frameworks, and the absence of performance-based training policies. It argues for the adoption of adaptive learning models, continuous professional development, and the strategic alignment of training programs with national economic and productivity objectives. Conceptually, it underscores the imperative for organizations to reframe training and development not as cost burdens, but as strategic investments with long-term performance dividends. The paper concludes that enhancing workforce capabilities through well-designed, context-specific, and technologically enabled training systems is critical to fostering organizational excellence and contributing to sustainable national development in Nigeria’s evolving economic landscape.